Ophiopogon rugosus (Asparagaceae), a new species from northeastern Vietnam - Tanaka, Noriyuki; Averyanov, Leonid V.; Nguyen, Cuong Huu; Maisak, Tatiana V.; Nguyen, Duong Tuan; Dai, Hai Vo; Chu, Quan Ngoc (Phytotaxa, 2025)
Ophiopogon rugosus, a new species from Thai Nguyen Province (formerly Bac Kan Province), NE Vietnam, is described and illustrated. It is distinguishable from all other members of the genus by its elliptic leaf blades with many small wrinckles arrayed in a checkered pattern on the adaxial surface. Somewhat resembling O. xylorrhizus in its habit and rigid roots, the new species clearly differs mainly by the smaller, adaxially wrinkled, abaxially white-glaucous (vs. pale green) leaf blades with fewer longitudinal parallel veins. Besides morphological and ecological data, we provide notes on its relationships to several similar species.